Pengaruh Peer Attachment terhadap Perilaku Bullying pada Siswa SMP di Kota Padang - Yusrarefin, M. Syukri; Aulia, Farah (TSAQOFAH, 2025)
Bullying is a recurring issue among adolescents, particularly in school environments, and has drawn serious attention from various stakeholders, including the Indonesian Child Protection Commission (Komisi Perlindungan Anak Indonesia, KPAI). This study aims to analyze the relationship between peer attachment and bullying behavior among junior high school students. A quantitative approach was employed, using a questionnaire distributed to 261 students from several junior high schools in Padang City. The sample was selected using a simple random sampling technique, based on the Isaac and Michael table with a 5% margin of error. The results show that students’ level of peer attachment falls within the high category (44.4% or 116 students), while bullying behavior is in the low category (52.9% or 138 students). Correlation analysis reveals a weak negative relationship between peer attachment and bullying behavior (r = -0.128), with validity coefficients ranging from 0.807–0.792 for peer attachment and 0.761–0.740 for bullying behavior. These findings indicate that higher levels of peer attachment are associated with a lower tendency to engage in bullying, and vice versa. This study contributes to the broader understanding of relational factors in the prevention of bullying behavior among adolescents.